Guianolactones A and B, Two Rearranged Pentacyclic Limonoids from the Seeds of Carapa guianensis. Issue 23 (2nd November 2017) - Higuchi, Keiichiro; Tani, Yoshimi; Kikuchi, Takashi; In, Yasuko; Yamada, Takeshi; Muraoka, Osamu; Tanaka, Naonobu; Tanaka, Reiko
Abstract: Two novel rearranged limonoids, guianolactones A (1 ) and B (2 ), were isolated from Carapa guianensis Aubl. (Meliaceae) seeds. The structures of1 and2 with their absolute configurations were elucidated in detailed examinations using single‐crystal X‐ray diffraction analyses and 2D NMR spectra. Guianolactone A (1 ) has a novel 5/6/6/6/6 pentacyclic core including two δ ‐lactone and a tetrahydropyran ring, while guianolactone B (2 ) is a novel limonoid with a 6/6/5/6/6 pentacyclic core featuring a δ ‐lactone and a tetrahydrofuran ring. Abstract : Two novel rearranged limonoids, guianolactones A (1 ) and B (2 ), were isolated from Carapa guianensis Aubl. (Meliaceae) seeds. The structures of1 and2 with the absolute configurations were determined by detailed examination of single‐crystal X‐ray diffraction analyses and 2D NMR spectra.